The Effect of Fundamental Motor Skills Training on Cognitive Impulsivity, Motor Impulsivity and Sustained Attention in Students with ADHD Symptoms - Seyedeh Bahar Banikarimi; Habib Hadianfard; Robabeh Rostami (University of Tehran, 2018)
Attention deficit/hyperactivity disorder (ADHD), is one of the common neurodevelopmental disorders in children, can produce several cognitive, social and educational difficulties. The purpose of this study is to investigate the effect of fundamental motor skills (FMS) on cognitive impulsivity, motor impulsivity and sustained attention in primary school children with attention deficit/hyperactivity disorder symptoms. The research method was quasi-experimental with pre-test-post-test design. The study population consists of all elementary school students of Shiraz schools. The sample used for the study was 38 students with ADHD symptoms which was selected by multi-level sampling based on SNAP-IV and randomly divided in two groups, experiment (21 subjects) and control (17 subjects). The experimental group trained for ten sessions in the FMS program and the control group dealt its daily activities. Then one session before and after of interventions all of the two groups were measured with using of continuous performance, dexterity, porteus maze and passing test. Data were analyzed by mixed repeated measures ANOVA and indicate that FMS training can have a positive effect on children performance in motor impulsivity, but there was no evidence of the effect of mentioned interventions on Cognitive impulsivity and sustained attention. According to the findings of the study, can be concluded that short term FMS training can be useful in controlling movement and impulses in children with ADHD symptoms.